Clinical Profile and Outcomes of Patients with Heat Stroke: An Observational Study from a Tertiary Care Center in Eastern India - Divendu Bhushan; Muskan Dogney; Deepak Kumar; Mohammed Iqbal; Vishal Vaibhaw (APIK Journal of Internal Medicine)
Background: Heat stroke is a growing public health concern exacerbated by rising temperatures and prolonged heat waves. This study examines the clinical profile, prognostic markers, and outcomes of heat stroke patients presenting to a tertiary care center in India and compares findings with previous global studies. Objective: The objective of this study was to analyze the clinical profile, prognostic markers, and outcomes of heat stroke patients presenting to a tertiary care center in India and to compare findings with previous global studies. Materials and Methods: A retrospective study was conducted between March and July 2024 at a tertiary care center in Eastern India. Data on demographics, clinical parameters, laboratory values, and outcomes were collected and analyzed using appropriate statistical methods. Results: During the study period, 43 patients were admitted with heat stroke, the mean age (in years) was 57, and 67% were male. The overall mortality rate was 21%. Significant predictors of mortality included hypotension (systolic blood pressure <100 mmHg, P = 0.040), tachypnea (respiratory rate >20/min, P = 0.001), Glasgow Coma Scale score <9 (P < 0.001), elevated creatinine, and multi-organ dysfunction syndrome involving the renal system and central nervous system (P < 0.01). Younger, active individuals were disproportionately affected due to occupational exposure to high ambient temperatures. Conclusion: Our findings highlight key clinical and biochemical predictors of poor outcomes in heat stroke. Indian patients, being younger and functionally active, may face increased exposure to high ambient temperatures.